Black feminist thinking and the blog “Blogueiras Negras” - Pereira da Silva, Thais (2021)
This article aims to reflect on the production of knowledge based on the epistemology of black feminist thought, proposed by Patricia Hill Collins, which is configured as a critical theory produced by black women in their struggles against three articulated dimensions of oppression: economic, political and ideological. In this paper, we analyze the ideological dimension, or the cultural dimension. For this, we use the Netnografia research method, from the analysis of the case study of the blog “Blogueiras Negras” (BN), which was carried out in the period from March 2013 to December 2014. Representative of the tradition of black printing and two movements of black women, or BN is a collaborative platform that brings together about 400 authors. In addition, the bibliographic research includes the following authors (s), also two cited: Sueli Carneiro, Lélia Gonzalez, among others.